Growth Performance and Carcass Quality in Broiler Chickens Fed on Legume Seeds and Rapeseed Meal - Biesek, Jakub (Animals (Basel), 2020)
SIMPLE SUMMARY: The production of broiler chickens is a dynamically developing industry. Most feeds are based on soybean meal as a source of protein. However, new challenges are arising in the meat production market, and consumers expect a wider range of products to choose from. There is potential in the production of broiler chickens fed on other sources of protein, e.g., legume seeds and rapeseed meal. The aim of this study was to investigate whether other sources of protein give similar results in terms of growth performance and meat quality compared to soybean meal diets. It was shown that the use of legume seeds and rapeseed meal did not affect most of the carcass characteristics and meat quality. However, the growth performance results were lower than when using soybean meal. Because they contained the smallest amount of antinutritional substances, faba beans are proposed as a possible partial replacement for soybean meal. ABSTRACT: The aim of this study was to compare the growth performance parameters, carcass quality, and meat traits in broiler chickens fed on diets containing legume seeds and rapeseed meal as an alternative to soybean meal. In this study, 448 male ROSS 308 chicks were divided into subgroups: a control group (I) fed on soybean meal (SBM), and six experimental groups II—rapeseed meal (RSM); III—white lupin (WY); IV—yellow lupin (YL); V—narrow-leaved lupin NLL; VI—pea (Pe); and VII—faba bean (FB). After 42 days of rearing, 10 birds from each group were slaughtered and dissected. The control group was characterized by better growth performance compared to the other groups. In addition, the European Broiler Index was lower in each experimental group compared to the SBM group. A lower dressing percentage was found only in the NLL group. The muscle content in birds from the RSM and FB groups was significantly higher than in the other groups, but the fat content was lower. Meat from SBM group was characterized by the highest protein content, but a reduced content of fat and water in the muscles. The most similar results were found between the control group and the FB group receiving a diet based on faba beans. Furthermore, lupins had a similar effect on the carcass traits when used in the diets. The quality of meat in broilers fed on faba beans with the addition of potato protein and brewers’ yeast was similar to that of those fed on soybean meal, because the antinutrients were the lowest in faba bean seeds. Faba beans are proposed as a possible alternative source of protein in poultry diets. Other legume seeds should be analyzed in future studies.